Evaluation of Public Service Performance of Disdukcapil through a Balanced Scorecard Approach - Zahra, Hemalia; Wahyu, Fitri Pebriani (Department of Public Administration, 2025)
This research provides the public service performance of the Bandung City Population and Civil Registration Service (Disdukcapil) in 2022 using the Balanced Scorecard (BSC) approach which includes four perspectives: financial, customer, internal processes, and learning and development. The analysis results show that budget efficiency reached 93.87%, reflecting good management although slightly below the target. The Community Satisfaction Index (IKM) of 91.09% is in the very good category, indicating high community satisfaction with the services provided. From an internal process perspective, performance achievement exceeded the target with a value of 100.97%, however there was a decrease in performance development of 1.65% compared to the previous year. Optimizing resources, innovation services, and increasing process efficiency are important focuses in strengthening integrity that is oriented towards community needs.